Enhancing Creativity Through the Development of Abstract Reasoning in Elementary School Children - Nasrul Fuad Erfansyah; Sulthon Mas`ud (JIEES : Journal of Islamic Education at Elementary School, 2023)
The enhancement of creativity in elementary school children has become an important concern in the context of modern education. This article aims to investigate the contribution of abstract reasoning development to the enhancement of creativity in elementary school children. Using a qualitative method with a literature review approach, this article presents a synthesis of the latest research that highlights the role of abstract reasoning in exploring children's creative potential. In-depth analysis of various approaches and practices of abstract reasoning development will be examined to identify effective strategies that can be adopted in the learning environment of elementary school children. The findings of this article are expected to provide a deeper understanding of the important role of abstract reasoning in enhancing children's creativity, providing a valuable contribution to the development of educational curricula that focus on the development of children's creativity from an early age.